Toxicology - New Aspects to This Scientific Conundrum 2016
DOI: 10.5772/64754
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicology: A Review

Abstract: Nanotoxicology represents a new and growing research area in toxicology. It deals with the assessment of the toxicological properties of nanoparticles (NPs) with the intention of determining whether (and to what extent) they pose an environmental or societal threat. Inherent properties of NPs (including size, shape, surface area, surface charge, crystal structure, coating, and solubility/dissolution) as well as environmental factors (such as temperature, pH, ionic strength, salinity, and organic matter) collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 68 publications
(90 reference statements)
1
7
0
Order By: Relevance
“…The results of the present investigation are in line with the studies reporting on the eco-toxicological impacts on marine ecosystems of E-NPs [1]. Studies on invertebrates and fishes have already suggested harmful effects of E-NPs exposure [20,38,39]. Our contribution to this area is given by pieces of evidence of the altered GRN expression and genotoxicity of C-NPs exposure in P. lividus embryos.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present investigation are in line with the studies reporting on the eco-toxicological impacts on marine ecosystems of E-NPs [1]. Studies on invertebrates and fishes have already suggested harmful effects of E-NPs exposure [20,38,39]. Our contribution to this area is given by pieces of evidence of the altered GRN expression and genotoxicity of C-NPs exposure in P. lividus embryos.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiological data showed adverse action of air-borne ultrafine particles on humans, which were confirmed in animal exposures [ 1 ]. Toxicity of metal, metal oxide and carbon-based nanoparticles (NPs) is most relevant for human health because exposure to this group of NPs is highest, occurs over long periods and degradation and excretion of the ingested particles are low [ 2 ]. Numerous studies have addressed adverse effects of NPs exposure by in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Released ions can diffuse inside the cell and block the active center of enzymes, deactivating the protein’s functionality. There are a plenty of recent reviews that focus on the toxic potential of materials at the nanolevel [ 79 , 80 , 81 , 82 , 83 ]. Exposure of the nanomaterial to UV can lead to electron-hole pairs’ activation and, consequently, bond splitting and radical formation.…”
Section: Nanotechnologymentioning
confidence: 99%